Тhe ПРАВО ОСУЂЕНИХ ЛИЦА НА ПОСЕТЕ ЧЛАНОВА ПОРОДИЦЕ И ОСТВАРИВАЊЕ КОНТАКАТА ВАН ЗАВОДА - Milić, Ivan; Grujić, Zdravko (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
The modern system of execution of the prison sentence, unlike the first classical systems of execution of this sentence, is based on the principles of individualization, resocialization and humane treatment of convicted persons. Adapting the method of execution of the prison sentence to the convicted person in order to achieve the purpose of punishment as efficiently as possible is the basic principle of the modern system of execution of the prison sentence or a prerequisite for the successful resocialization of the convicted person. The principle of humane treatment of convicted persons is based on prescribing the basic (minimum) rights of convicts serving prison sentences by national legal regulations, but also establishing minimum legal standards at the regional and global international level. Bearing in mind the conformity of the legislation of the Republic of Serbia with the standards prescribed by international sources in the field of the rights of persons deprived of their liberty, the right of convicted persons to visits by family members and establish contacts with the outside world represent a significant factor in achieving the resocialization of convicted persons and a prerequisite for their successful reintegration into social community.The rights of convicted persons serving prison sentences in penal institutions differ, first of all, depending on whether it is the general population of convicts or, on the other hand, the so-called special categories of persons sentenced to imprisonment. One of the basic rights of convicted persons serving their prison sentence in a penitentiary is the right to be visited by family members. The subject of the author's attention is precisely the right to visit family members, but also to have other contacts with the outside world. It is a right that, basically, all categories of convicted persons have, but the right to visits by family members, the scope and frequency of visits differs depending on the category and position of the convicted person in the institution and the possibility of using the extended rights (conveniences) of the convicted person.
Keywords: convict, prison sentence, imprisonment, family member, prison, rights of convicts, right to visits by family members